Renal artery occlusion in the late postoperative period managed with renal artery stenting after endovascular abdominal aortic aneurysm repair and renal function salvage - Mustafa Serkan Karakaş; Necmettin Korucuk; Cemal Kemaloğlu; Refik Emre Altekin; İbrahim Demir (KARE Publishing, 2017)
Endovascular aneurysm repair (EVAR) of abdominal aorta is a valuable treatment option in selected patients with abdominal aortic aneurysm. Renal artery occlusion is a serious complication after EVAR and may progress to permanent renal injury requiring hemodialysis. In this report, case of unexpected renal artery occlusion after EVAR treated with renal artery stenting in the late postoperative period is described.